The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1634/theoncologist.2015-0056
|View full text |Cite
|
Sign up to set email alerts
|

Media Reporting of Practice-Changing Clinical Trials in Oncology: A North American Perspective

Abstract: Introduction. Media reporting of clinical trials impacts patient-oncologist interactions. We sought to characterize the accuracy of media and Internet reporting of practice-changing clinical trials in oncology. Materials and Methods. The first media articles referencing 17 practice-changing clinical trials were collected from 4 media outlets: newspapers, cable news, cancer websites, and industry websites. Measured outcomes we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 63 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…3 Additionally, providing outcomes directly to participants is more accurate than the often sensationalized, incomplete, or exaggerated claims purported by mainstream media. 912 However, some authors have identified potential pitfalls of disclosure, including emotional distress from negative results, 13 release of premature outcomes, and the time or cost constraints that limit the ability to disclose information effectively. 1315…”
Section: Introductionmentioning
confidence: 99%
“…3 Additionally, providing outcomes directly to participants is more accurate than the often sensationalized, incomplete, or exaggerated claims purported by mainstream media. 912 However, some authors have identified potential pitfalls of disclosure, including emotional distress from negative results, 13 release of premature outcomes, and the time or cost constraints that limit the ability to disclose information effectively. 1315…”
Section: Introductionmentioning
confidence: 99%
“…Other consumer and patient sources – In a systematic review of studies assessing the quality of online health information for consumers, Eysenbach et al found 55 of 79 studies (70%) had concluded that quality was a problem. 71 In more recently published studies, others have found problems with the information on anti-vaccination websites, 72 cancer and oncological industry websites, 73 websites for clinics offering weight loss surgery, 74 and websites for fertility centres. 75 In their study of media coverage of practice-changing clinical trials in oncology, Andrew et al .…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 17 practice-changing clinical trials, it has been demonstrat- ed that a media reporting score, defined as a measure of completeness of information detailed in media articles, showed most thorough reporting for industry, followed by cancer websites (including www.ascopost.com, www. cancer.org and www.cancer.gov), newspapers as well as cable news [14]. The most frequently excluded items from media coverage were study limitations, followed by exclusion criteria, adverse events, and conflicts of interest.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are several important limitations of published studies. First, only a small number of RCTs have been explored and searching of media coverage was not systematic and therefore likely incomplete [14,15]. Second, analyses included primarily media reporting from eminent scientific meetings and were not based on research findings published in peer-reviewed medical journals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation